Esters of quinoxaline-7-carboxylate-1,4-di-N-oxide as Trichomonas vaginalis triosephosphate isomerase inhibitors - Palos Isidro; Moo-Puc Rosa; Vique-Sánchez José Luis; Benítez-Cardoza Claudia G.; Monge Antonio; Villalobos-Rocha Juan Carlos; Paz-Gonzalez Alma D.; Rivera Gildardo (Acta Pharmaceutica)
Trichomoniasis is a public health problem worldwide. Trichomoniasis treatment consists of the use of nitroimidazole derivatives; however, therapeutic ineffectiveness occurs in 5 to 20 % of the cases. Therefore, it is essential to propose new pharmacological agents against this disease. In this work, esters of quinoxaline-7-carboxylate-1,4-di-N-oxide (EQX-NO) were evaluated in in vitro assays as novel trichomonicidal agents. Additionally, an in vitro enzyme assay and molecular docking analysis against triosephosphate isomerase of Trichomonas vaginalis to confirm their mechanism of action were performed. Ethyl (compound 12) and n-propyl (compound 37) esters of quinoxaline-7-carboxy-late-1,4-di-N-oxide derivatives showed trichomonicidal activity comparable to nitazoxanide, whereas five methyl (compounds 5, 15, 19, 20 and 22), four isopropyl (compounds 28, 29, 30 and 34), three ethyl (compounds 4, 13 and 23) and one npropyl (compound 35) ester derivatives displayed activity comparable to albendazole. Compounds 6 and 20 decreased 100 % of the enzyme activity of recombinant protein triosephosphate isomerase.